Apports, limites et perspectives des méthodes « classiques » de datation du bâti en milieu rural : quelques exemples dans les vallées de la Baïse et du Lot - Alain Beschi (In Situ)
The inventory campaigns carried out over the last few years in the Aquitaine region, on the Baïse and Lot valleys, have applied generalist methods to the problems of dating buildings in rural contexts. These methods require the elaboration of reliable criteria and the constitution of tools and references of a chrono-typological nature. The examples presented in this article suggest that beyond the mere accumulation of information on the heritage of this territory, the inventory campaigns, through their chronological analyses, make a real contribution to the interpretation of the history of the French countryside.